KONSIDERANS PEMILIH DI KABUPATEN KLUNGKUNG PADA PEMILIHAN PRESIDEN MENGGUNAKAN ANALISIS FAKTOR - YUKESANI, MADE HARISA; SUKARSA, I KOMANG GDE; JAYANEGARA, KETUT; KENCANA, I PUTU EKA N.; OCTAVANNY, MADE AYU DWI; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 13 No 4 (2024)DO - 10.24843/MTK.2024.v13.i04.p466, 2024)
Presidential election is an implementation of popular sovereignty. Voters in presidential election come from various backgrounds and each of them have their own political perceptions. This study aims to determine factors that influence voters’ considerations in Klungkung regency. Population in this study consist of Klungkung residents who are eligible to vote. Using purposive sampling, 110 people were selected as respondents. Data for this study was collected using questionnaires from February to April 2024. Exploratory Factor Analysis (EFA) was used to find the underlying determinant of voters’ considerations. The results shows there are 8 factors that influence voters’ considerations in Klungkung. These factors are (1) candidate’s policies and experience; (2) candidate’s background; (3) money politics; (4) ideological alignment and track record; (5) candidate’s campaign; (6) candidate’s firmness and popularity; (7) candidate's work program and candidate closeness to the people; and (8) candidate's vision and mission. These factors explain 68% of the variance in voters’ considerations.